The Shifting Center: The Global South’s Rising Role in Future Higher Education - Knobel, Marcelo (International Higher Education, 2025)
<h3 id="this-article-examines-how-demographic-shifts-and-changing-knowledge-production-patterns-are-repositioning-the-global-south-from-the-periphery-to-the-center-of-future-higher-education-as-africas-youth-population-grows-and-southern-research-networks-expand-traditional-northsouth-dynamics-are-transforming-to-maintain-relevance-in-this-evolving-landscape-higher-education-institutions-must-develop-new-frameworks-that-recognize-the-global-souths-strengths" data-pm-slice="1 1 []">This article examines how demographic shifts and changing knowledge production patterns are repositioning the Global South from the periphery to the center of future higher education. As Africa’s youth population grows and Southern research networks expand, traditional North–South dynamics are transforming. To maintain relevance in this evolving landscape, higher education institutions must develop new frameworks that recognize the Global South’s strengths.